Endoscopic comparison of gastroduodenal injury with over-the-counter doses of new fast-dissolving ibuprofen and paracetamol formulations: a randomized, placebo-controlled, 4-way crossover clinical trial - Lanza, Frank L (Clin Exp Gastroenterol, 2018)
BACKGROUND: While gastrointestinal (GI) effects of standard ibuprofen and N-acetyl-p-aminophenol (APAP) have been reported, upper GI injury following treatment with fast-dissolving (FD) formulations of these analgesics has not been investigated. We evaluated upper GI effects of over-the-counter doses of 2 FD ibuprofen products and 1 FD-APAP product. METHODS: In a randomized, placebo-controlled, endoscopist-blinded, 4-way crossover study, 28 healthy subjects received FD ibuprofen 2×200 mg liquid capsules 3 times daily (TID), ibuprofen 2×200 mg tablets TID, FD-APAP 2×500 mg tablets 4 times daily (QID), and placebo 2×500 mg tablets QID for 7 days. The primary end point was gastric mucosal damage assessed by endoscopy using the Lanza scale: 0=normal stomach or proximal duodenum, 1=mucosal hemorrhages only, 2=1 or 2 erosions, 3=numerous (3–10) erosions, and 4=large number of erosions (>10) or ulcer. Secondary end points included duodenal mucosal damage (Lanza scale); gastroduodenal mucosal injury, classified as present (gastric and/or duodenal endoscopy score ≥2) or absent (gastric and/or duodenal endoscopy score <2); and number of hemorrhages, erosions, and ulcers counted separately in the stomach and duodenum. RESULTS: Significantly greater gastric mucosal injury was observed after treatment with both ibuprofen products vs FD-APAP (p<0.0001 and p=0.0095, respectively). FD-APAP showed no difference from placebo (p=0.4794). The odds of having an incidence of gastroduodenal mucosal injury were over 6 times greater from FD ibuprofen liquid capsule treatment (odds ratio [OR]=6.19, 95% confidence interval [CI]: 1.60, 23.97) and over 3 times greater from ibuprofen tablet treatment (OR=3.19, 95% CI: 0.8, 12.74) vs FD-APAP. CONCLUSION: Treatment with 2 ibuprofen products was associated with significant gastric mucosal injury. Of the 4 treatments studied, FD ibuprofen liquid capsules had the highest risk of incidence of gastroduodenal mucosal injury. Treatment with FD-APAP did not induce any clinically or statistically significant gastroduodenal mucosal injury.